Neology of Arabic in Indonesia - Sukiman, Uki (Universitas Islam Negeri Raden Intan Lampung, 2020)
The development of Arabic which is influenced other language and culture is very interesting to be discussed, because Arabs themselves are not able to give a name to something that does not exist in their nature and their thought, such as naming cases, and terms that come from language and nature of thought of Indonesians. Many of these new words and terms have been featured in one of the Arabic language magazines which is Alo Indonesia. This study aims to find out how the names and terms in Indonesian discourse influenced Arabic and the problems that arise in the process of producing words in the magazine. This research is literature research that used descriptive methods, namely describing the data by concerning to how the use of new Arabic words and terms in Alo Indonesia magazine. The data collection method is done by using the “note-taking” technique which is then collected in the data card. To answer the two main problems above, the writer used Ibrahim Murad's theory of neology. The findings of this study shows that according to five theories by Ibrahim Murad, Alo Indonesia magazine uses more semantic neology theory (al-Taulĩd al-Dalalĩ) and loan neology (al-Taulĩd bi al-Iqtirād). The biggest problem in the transliteration process from Indonesian letters into Arabic is that not all vowels and consonants in Indonesian are also available simultaneously in Arabic, and so does the difficulty of finding the equivalent of idea in the expression of these two languages.